Immunohistochemical expression of galectin-3 in carcinoma of uterine cervix - ., Chandershekhar; Singh, Gajender; Dhankher, Monika; Cheran, Zeany (International Journal of Research in Medical Sciences, 2022)
Background: Cervical cancer is one of the most common cancer among women worldwide, second to breast cancer. It’s difficult to diagnose in the early stage due to subtle and non-specific symptoms. Galectin-3 is increasingly being recognized as an important regulator of a broad range of cancer cell activities including cervical cancer. Its expression depends on the tumor grade which signifies its role in progression of the disease and prognostic significance. Method: The present study was conducted in department of pathology, Pt. B. D. Sharma PGIMS, Rohtak on 60 cases of histo-pathologically diagnosed squamous cell carcinoma of uterine cervix. Immunohistochemical (ICH) expression of marker ‘Galectin-3’was assessed in all biopsy specimens. Results: Galectin-3 expression was 1+ in 83.3% cases and 2+ in 16.6% cases of grade 1 cervix carcinoma. In grade 2 carcinomas 55.3% showed 1+, 42.1% showed 2+ and 2.6 % cases showed 0 galectin -3 expression. Further, 70% of grade III cases showed a score of 2+, and 10 % showed 1+ expression and 20 % didn’t show any galectin 3 positivity. A statistically significant association of galectin-3 expression with histological grade was observed. Conclusions: IHC expression of galectin-3 can be used as an important marker for grading of cervical carcinoma, therefore the present study was done to evaluate the IHC expression of galectin 3 in cervical cancer and correlate it with histologic tumour grade.